Asymmetric Synthesis of 1-Benzazepine Derivatives via Copper-Catalyzed Intramolecular Reductive Cyclization - Li, Dingxi; Park, Yeji; Yoon, Woojin; Yun, Hoseop; Yun, Jaesook (Organic Letters, 2019)
An asymmetric construction of enantioenriched 2,3-substituted-1-benzazepine derivatives containing a cyclic tertiary amine moiety was developed by copper-catalyzed reductive intramolecular cyclization of (E)-dienyl arenes with a tethered ketimine. This protocol involves tandem chemo-, regio-, and enantioselective hydrocupration and asymmetric cyclization in the presence of a chiral bisphosphine-copper catalyst. Under mild conditions, a broad range of 1-benzazepine derivatives was obtained in good to high yields with high degrees of diastereoselectivity and enantioselectivity.